A rare association of Down syndrome with Dandy –Walker variant, pulmonary hypertension and childhood interstitial lung disease: A case report of a prognostic dilemma. Issue 6 (December 2022) - Mohd Kori, Anis M.; Alias, Amelia; Daud, Mariana; Yahaya, Nor A.; Anuar, Muhamad A.
الملخص: المقدمة: تعتبر العلاقة بين متلازمة داون، داندي- ووكر المتغير، ارتفاع ضغط الشريان الرئوي ومرض الرئة الخلالي في مرحلة الطفولة نادرة للغاية. تم الإبلاغ عن العديد من الحالات بين اضطرابات التثلث الصبغي مع تشوه داندي- ووكر ونتائج النمو العصبي. بصعوبة الحالة وتعقيدها مع القناة الشريانية السالكة، ارتفاع ضغط الشريان الرئوي ومرض الرئة الخلالي في مرحلة الطفولة، وجب علينا دراسة امتداد ارتفاع ضغط الشريان الرئوي سواء كان متوسطا الى شديدا والذي يؤدي الى امراض ووفيات كبيرة عند الرضع المصابين بمتلازمة داون وتشوه داندي- ووكر تقرير حالة: نبلغ عن حالة لطفلة خديجة - تبلغ خمسة عشر- شهرا, تأكدت اصابتها بمتلازمة داون و داندي- ووكر المتغير والتي أصيبت بارتفاع ضغط الشريان الرئوي ومرض الرئة الخلالي في مرحلة الطفولة الاستنتاجات: هذه هي الحالة الأولى من نوعها مع وجود العديد من الارتباطات المعقدة التي تم الإبلاغ عنها تتضمن متلازمة داون وداندي- ووكر المتغير. أدت هذه الحالة الى معضلة في التشخيص واستشارة الوالدين الرحيمة حيث ان المستقبل غير معروف Abstract: Associations among Down syndrome (DS), Dandy–Walker variant (DWv), pulmonary hypertension (PH) and childhood interstitial lung disease (chILD) are extremely rare. Several cases of trisomy disorders with Dandy–Walker malformation (DWM) and neurodevelopmental outcomes have been reported. The extent to which moderate to severe pulmonary hypertension with complications of patent ductus arteriosus (PDA), PH and chILD leads to substantial morbidity and mortality in infants with DS and DWM should be studied. We report the case of an ex-premature 15-month-old girl with confirmed DS with DWv, who developed PH and chILD. This is the first case study reporting the complexity of multiple associations involving DS and DWv. This case led to a prognostic dilemma and required compassionate parental counselling because of the child's uncertain future.